Attitudinal and behavioural differences towards farm animal welfare among consumers in the BRIC countries and the USA - Mata, F.; Dos-Santos, M. J. P. L.; Cocksedge, J. (Sustainability, 2023)
This study explores cross-cultural differences in consumers’ attitudes toward farm animal welfare (FAW) in BRIC countries. Questionnaires administered in each country contained the following questions: (i) “It is important to me that animals used for food are well cared for”, (ii) “The typical nationality thinks it is important that animals used for food are well cared for”, (iii) “Low meat prices are more important than the well-being of animals used for food”, and (iv) “The typical nationality thinks that low meat prices are more important than the well-being of animals used for food”. Answers were given on a Likert scale (from total disagreement to total agreement). Data fit multinomial logistic models using “Country” and “Gender” as factors and “Age” as a covariate. The results showed that women had stronger pro-animal attitudes. Statements on the perception of FAW importance had an agreement tendency that increased with age, while the opposite was true for meat prices. Brazil showed the highest levels of individual pro-FAW attitudes, and the same trend in relation to meat prices. Russia showed a slightly lower pro-FAW attitude, but the perception of the compatriots’ attitudes towards FAW showed the opposite. Russians in general disagree with low meat prices in exchange for the detriment of FAW. Indians were the least supportive of FAW and, together with the Chinese, were the least supportive of an increase in meat prices to improve FAW. The Chinese showed prominent levels of neutrality towards FAW. These results may contribute to the definition of food and trade policies and help to adjust the supply chain to consumers’ socio-cultural and economic differences.